Main components and human health risks assessment of PM10, PM2.5, and PM1 in two areas influenced by cement plants. (November 2015) - Sánchez-Soberón, Francisco; Rovira, Joaquim; Mari, Montse; Sierra, Jordi; Nadal, Martí; Domingo, José L.; Schuhmacher, Marta
Abstract: Particulate matter (PM) is widely recorded as a source of diseases, being more harmful those particles with smaller size. PM is released to the environment as a consequence of different activities, being one of them cement production. The objective of this pilot study was to characterize PM of different sizes around cement facilities to have a preliminary approach of their origin, and evaluate their potential health risks. For that purpose, three fractions of PM (10, 2.5, and 1) were collected in the nearby area of two cement plants with different backgrounds (urban and rural) in different seasons. Subsequently, main components, outdoor and indoor concentrations, exposure, and human health risks were assessed. Greatest levels of PM1, organic matter, and metals were found in urban location, especially in winter. Consequently, environmental exposure and human health risks registered their highest values in the urban plant during wintertime. Exposure was higher for indoor activities, expressing some metals their peak values in the PM1 fraction. Non-carcinogenic risks were below the safety threshold (HQ < 1). Carcinogenic risks for most of the metals were below the limit of 10 −5, except for Cr (VI), which exceeded it in both locations, but being in the range considered as assumable (10 −6 –10 −4 ). Highlights: Characterisation of PM10, PM2.5, and PM1 was carried out around two cement plants. Outdoor and indoor exposure and human health risk to toxic elements were assessed. Higher concentrations and human health risks were observed in urban site in winter. Maximum human health risk levels were found due to PM1 fraction exposure.